Development of the Evaluation Index System in Internal Governance Ability of Social Sports Associations in Guangdong Province - Li, Jialin; Hongseanyatham, Prakit (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: As a major sports province in China, Guangdong Province has always attached great importance to the development of sports and actively responded to the national policy deployment. Through the research on the internal governance of provincial social sports associations in Guangdong Province, the internal governance evaluation index system is established it is beneficial to the comprehensive development of social sports associations and better service for the national fitness cause, but it also conducive to the government to timely understand the current situation of social associations, more reasonable allocation of resources, overall layout. The objective of this research was to develop the evaluation index system for the internal governance ability of social sports associations in Guangdong Province. Materials and Methods: In this research, the sample group consisted of 65 Guangdong Provincial social sports associations. A literature review, questionnaire, and interviews with seven experts were conducted to investigate the current situation of the internal governance ability of social sports associations in Guangdong Province. Based on the current situation, the researcher would draft the Delphi question framework. After that, 19 experts were invited to conduct the Delphi consensus. After three rounds of Delphi consensus, the evaluation index of the internal governance ability of social sports associations was formulated. Then, seven experts were invited to perform the connoisseurship to evaluate and revise the indicator system. Finally, by conducting an on-site investigation of 15 social sports associations in Guangdong Province, the actual operation of the index system is verified, and the development status of social sports associations in Guangdong Province is preliminarily judged according to the index system. The mean, standard deviation, median, and interquartile range were used to analyze the data. Results: The evaluation index system of the internal governance ability of social sports associations consists of 5 first-level indicators, respectively: Institutional Framework, Human Resource Management, Financial Asset Management, Archive Seal Management, and Development Planning. These indicators include 18 second-level indicators and also includes 39 third-level indicators. Conclusion: The internal governance evaluation index system of social sports associations that has been established has played a positive role in improving the governance level of associations and promoting the development of social sports undertakings. In the future, we will continue to listen to the opinions and suggestions of experts and constantly optimize and improve the index system to better adapt to the needs and challenges of the development of the association and promote the long-term, comprehensive, and orderly development of the social sports association.